COMPARISON BETWEEN DIETARY INTAKE AND AGE IN RELATION TO BODY MASS INDEX AMONG POLYCYSTIC OVARIAN SYNDROME WOMEN – A CASE–CONTROL STUDY - BRINDHA G; MADHANSHANKAR SR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Polycystic ovarian syndrome (PCOS) is the most prevalent endocrine disorder, affecting up to 6.8% of women at their prime reproductive age. The aim of the study is to prove the interrelationship between food patterns, age, and anthropometric measurements in relation with body mass index (BMI) among PCOS women and control participants. Methods: The study was performed among 80 PCOS women and control participants according to the Rotterdam criteria. The data were collected through questionnaire which included age, socioeconomic data, anthropometric details, and food pattern, and the values were analyzed using Minitab 17 by Box plot method for graphical representation. The comparative analysis between age group and BMI was done by ANOVA. Results: The results showed that there was significant relationship between inappropriate food pattern and PCOS women showing higher frequency of ±8.30 among age group (19-24 years) with an average BMI of 31.6 kg/m2. The unhealthy diet along with BMI was correlated with the visual examination of presence of hirsutism. From the ANOVA analysis, it was significantly proved with probability (p=0.002); there was stronger association between lifestyle modifications and PCOS. This is the first association study to correlate between dietary habitat and age group with BMI among South Indian in Coimbatore district. Conclusion: From the results obtained, it is necessary to create awareness for women and girls about the ill effects of lifestyle modifications, unhealthy food pattern, and lack of physical activity which lead hormonal and metabolic changes.